Globalization and the Politics of Translation Studies - Pym, Anthony (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractGlobalization can be seen as a consequence of technologies reducing the costs of communication. This reduction has led both to the rise of English as the international lingua franca and to an increase in the global demand for translations. The simultaneous movement on both fronts is explained by the divergent communication strategies informing the production and distribution of information, where translation can only be expected to remain significant for distribution, and not for production. The fundamental change in the resulting communication patterns is the emergence of one-to-many document production processes, which are displacing the traditional source-target models still used in Translation Studies. Translation Studies might nevertheless retain a set of political principles that could constitute its own identity with respect to globalization. Such principles would be expressed in the national and regional organization of the discipline, in the defense of minority cultures, and in a general stake in cultural alterity. The possible existence of such principles is here examined on the basis of three instances where Translation Studies might address globalization in political terms: the weakness of the discipline in dominant monocultures, the development of an international association of Translation Studies, and political boycotts of translation scholars.